Optical and Electrochemical Study of Acridine‐Based Polyaza Ligands for Anion Sensing. Issue 23 (8th June 2018) - Bettazzi, Francesca; Voccia, Diego; Bencini, Andrea; Giorgi, Claudia; Palchetti, Ilaria; Valtancoli, Barbara; Conti, Luca
Abstract : A variety of transition metal organometallic and coordination receptor systems that can recognize and sense anionic guest species in organic and aqueous media by electrochemical and optical methods have already been reported in literature. In many cases, a redox‐active/photo‐active transition metal reporter group is used. Here, we describe two novel molecules consisting of a polyaza receptor unit for anion coordination and an acridine moiety as signal generating unit for anion sensing. The optical and electrochemical behavior of the two compounds was investigated in order to define novel detection schemes. In this regard, selenium anionic species selenite (SeO3 2– ) and selenate (SeO4 2– ) were chosen as model system. Abstract : Polyamine ligands containing an acridine moiety can be successfully employed as dual channeling chemosensors for selenite/selenate in aqueous media.